Step
*
2
2
2
of Lemma
KozenSilva-corollary2
1. x : Atom
2. y : Atom
3. ¬(x = y ∈ Atom)
4. k : ℤ
5. 0 < k
6. d : ℕ ⟶ ℕ
7. X : PowerSeries(ℤ-rng)
8. Π(i∈upto(k - 1)).(((k - 1 - i)*atom(x)+atom(y)))^(d (i + 1)) = X ∈ PowerSeries(ℤ-rng)
9. N : ℕ
10. Σ(d (i + 1) | i < k - 1) = N ∈ ℕ
⊢ (X[bag-rep(N;x)] = Π((k - 1 - i)^(d (i + 1)) | i < k - 1) ∈ ℤ)
⇒ (((((k)*atom(x)+atom(y)))^(d 0)*X)[bag-rep((d 0) + N;x)] = Π((k - i)^(d i) | i < k) ∈ ℤ)
BY
{ TACTIC:(Subst ⌜Π((k - i)^(d i) | i < k) ~ k^(d 0) * Π((k - 1 - i)^(d (i + 1)) | i < k - 1)⌝ 0⋅
THENM (GenConcl ⌜Π((k - 1 - i)^(d (i + 1)) | i < k - 1) = u ∈ ℤ⌝⋅ THENA Auto)
) }
1
.....equality..... 
1. x : Atom
2. y : Atom
3. ¬(x = y ∈ Atom)
4. k : ℤ
5. 0 < k
6. d : ℕ ⟶ ℕ
7. X : PowerSeries(ℤ-rng)
8. Π(i∈upto(k - 1)).(((k - 1 - i)*atom(x)+atom(y)))^(d (i + 1)) = X ∈ PowerSeries(ℤ-rng)
9. N : ℕ
10. Σ(d (i + 1) | i < k - 1) = N ∈ ℕ
⊢ Π((k - i)^(d i) | i < k) ~ k^(d 0) * Π((k - 1 - i)^(d (i + 1)) | i < k - 1)
2
1. x : Atom
2. y : Atom
3. ¬(x = y ∈ Atom)
4. k : ℤ
5. 0 < k
6. d : ℕ ⟶ ℕ
7. X : PowerSeries(ℤ-rng)
8. Π(i∈upto(k - 1)).(((k - 1 - i)*atom(x)+atom(y)))^(d (i + 1)) = X ∈ PowerSeries(ℤ-rng)
9. N : ℕ
10. Σ(d (i + 1) | i < k - 1) = N ∈ ℕ
11. u : ℤ
12. Π((k - 1 - i)^(d (i + 1)) | i < k - 1) = u ∈ ℤ
⊢ (X[bag-rep(N;x)] = u ∈ ℤ) 
⇒ (((((k)*atom(x)+atom(y)))^(d 0)*X)[bag-rep((d 0) + N;x)] = (k^(d 0) * u) ∈ ℤ)
Latex:
Latex:
1.  x  :  Atom
2.  y  :  Atom
3.  \mneg{}(x  =  y)
4.  k  :  \mBbbZ{}
5.  0  <  k
6.  d  :  \mBbbN{}  {}\mrightarrow{}  \mBbbN{}
7.  X  :  PowerSeries(\mBbbZ{}-rng)
8.  \mPi{}(i\mmember{}upto(k  -  1)).(((k  -  1  -  i)*atom(x)+atom(y)))\^{}(d  (i  +  1))  =  X
9.  N  :  \mBbbN{}
10.  \mSigma{}(d  (i  +  1)  |  i  <  k  -  1)  =  N
\mvdash{}  (X[bag-rep(N;x)]  =  \mPi{}((k  -  1  -  i)\^{}(d  (i  +  1))  |  i  <  k  -  1))
{}\mRightarrow{}  (((((k)*atom(x)+atom(y)))\^{}(d  0)*X)[bag-rep((d  0)  +  N;x)]  =  \mPi{}((k  -  i)\^{}(d  i)  |  i  <  k))
By
Latex:
TACTIC:(Subst  \mkleeneopen{}\mPi{}((k  -  i)\^{}(d  i)  |  i  <  k)  \msim{}  k\^{}(d  0)  *  \mPi{}((k  -  1  -  i)\^{}(d  (i  +  1))  |  i  <  k  -  1)\mkleeneclose{}  0\mcdot{}
THENM  (GenConcl  \mkleeneopen{}\mPi{}((k  -  1  -  i)\^{}(d  (i  +  1))  |  i  <  k  -  1)  =  u\mkleeneclose{}\mcdot{}  THENA  Auto)
)
Home
Index